2009
DOI: 10.1002/j.0022-0337.2009.73.2.tb04657.x
|View full text |Cite
|
Sign up to set email alerts
|

Behavior‐Associated Self‐Report Items in Patient Charts As Predictors of Dental Appointment Avoidance

Abstract: Dentally anxious patients with long-term avoidance behavior may experience treatment complications and induce stress in the dentist. Since dental anxiety scales are seldom used clinically, it is valuable to investigate the strength of behavior-associated items in the current patient chart in predicting canceled or missed appointments. Charts from a sample of patients (N=357) who visited the UCLA Dental Center January 2006 to June 2006 were examined for self-reports of depression, moodiness, nervousness, and an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 17 publications
1
3
0
Order By: Relevance
“…In this decision tree, other factors such as gender, age, urgent need, and payment type also showed some association, but it was seeking health information that split the group and placed 70% of all people who FTS into one group. Similar to other investigators, we found that public insurance (Medicaid) was not a strong predictor of FTS for dental visits .…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In this decision tree, other factors such as gender, age, urgent need, and payment type also showed some association, but it was seeking health information that split the group and placed 70% of all people who FTS into one group. Similar to other investigators, we found that public insurance (Medicaid) was not a strong predictor of FTS for dental visits .…”
Section: Discussionsupporting
confidence: 90%
“…Although we focus on the US in this paper, numerous researchers in other countries have also investigated FTS . Forgetting the appointment and illness are frequently cited as reasons for FTS; however, the literature is inconsistent as to other factors . Factors related to difficulty in canceling appointment (e.g., no telephone, called but could not get through), a long lag time between appointments, and having conflicting time commitments ; not seeing the dental service as valuable ; lack of trust in the dental health care system ; and health issues (e.g., illness, negative emotionality, mental health) have been shown to be associated with an increased risk of FTS.…”
mentioning
confidence: 99%
“…Proposed psychological barriers that bear a conceptual relationship to broken appointments include a range of experiences ranging from dental fear and avoidance, to symptoms of mental health diagnoses that impact self‐care, to limitations in working memory or executive functioning that make organization and follow‐through more difficult. One retrospective study was able to predict broken or canceled dental appointments using chart notations of self‐reported moodiness, depression, and prior appointment avoidance due to dental fear , and survey research does suggest some connection between missed appointments and dental anxiety . Some psychiatric symptoms have been found to impact self‐care in general and oral self‐management specifically .…”
Section: Discussionmentioning
confidence: 99%
“…The demographic characteristics that have been associated with lower rates of appointment‐keeping include self‐pay for dental care, rural residence, adolescent age ; use of public assistance, greater distance from home to clinic, lower educational attainment, and race, with non‐Whites having higher broken appointment rates than Whites . Psychosocial characteristics associated with lower rates of appointment‐keeping include significant debt ; having a resident rather than a faculty member as the dental provider ; lack of a working phone, previous history of broken appointments ; lower health literacy scores ; dental fear ; common fears ; and self‐reported depression, moodiness, and prior appointment avoidance due to dental fear . The practice of scheduling different members of the same family on the same day, or ‘batch appointments’, has been associated with higher clinicwide rates of broken appointments ; however, clinics must weigh this risk against the finding that prior dental visits at the same clinic by children from the same household are associated with a delay in caries onset .…”
Section: Methodsmentioning
confidence: 99%